Much ado about nothing: A failed case for banning combustion vehicles - García, Carmen; Jiménez, Juan Luis; Perdiguero, Jordi (Estudios de Economía, 2023)
The Balearic Islands (Spain) passed a regional law in 2019 banning the registration of diesel and petrol vehicles from 1 January 2025 and 1 January 2035, respectively. This law was heavily criticised before and during its implementation and was finally abolished after six months. This paper analyses the effect of this law on the registrations of both types of vehicles, as well as the registration of non-polluting vehicles. Both the synthetic control method and the difference-in-difference estimator show that the ban had no impact on any type of vehicle, not even on those that are non-polluting. Although the Balearic Islands’ regional government sought to pioneer implementation of this policy, the incorrect specification of the law, the uncertainty surrounding its approval and its short-term effects and may have reduced its effectiveness.